The laws of the city. (Economist, 2012)
The article discusses urban research in cities around the world as of June 2012, focusing on the collection of data on cities and its use in urban planning and management. Some sources of urban data include historical census and population records, telecommunications records, and microblog messages posted on the social media network Twitter.